Advances in protein subunit vaccines against H1N1/09 influenza - Zhang, Yu; Gao, Jingyao; Xu, Wenqi; Huo, Xingyu; Wang, Jingyan; Xu, Yirui; Ding, Wenting; Guo, Zeliang; Liu, Rongzeng (Frontiers in Immunology, 2024)
The A/H1N1pdm09 influenza virus, which caused the 2009 pandemic, has since become a recurring strain in seasonal influenza outbreaks. Given the ongoing threat of influenza, protein subunit vaccines have garnered significant attention for their safety and effectiveness. This review seeks to highlight the latest developments in protein subunit vaccines that specifically target the A/H1N1pdm09 virus. It will also examine the structure and replication cycle of influenza A viruses and compare different types of influenza vaccines. Additionally, the review will address key aspects of H1N1 protein subunit vaccine development, such as antigen selection, protein expression systems, and the use of adjuvants. The role of animal models in evaluating these vaccines will also be discussed. Despite challenges like antigenic variability and the complexities of vaccine production and distribution, protein subunit vaccines remain a promising option for future influenza prevention efforts.